Detailed Examination of Domain Wall Types, Their Widths and Critical Diameters in Cylindrical Magnetic Nanowires - Altbir-Drullinsky, D (Elsevier B.V., 2022)
Understanding and mastering the magnetic properties of domain walls in cylindrical nanowires is a fundamental pillar for developing novel 3D information technologies. For this purpose, a good comprehension of domain wall (DW) dynamical properties, which are strongly dependent on its type and size, is needed. In this work, by means of micromagnetic simulations, we focus on the accurate determination of DW types (transverse, vortex-antivortex, and the Bloch point) and DW widths and present a state diagram as a function of the diameter and the nanowire material. Using different initial states and trajectories we find a large region of metastability where the Bloch-point domain wall co-exists with either transverse or a more energetical vortex-antivortex one. We determine the domain wall width and its dependence on the nanowire diameter either for the transverse or the vortex-antivortex domain wall showing that it is always larger than the nanowire diameter. We also find simple expressions for the DW widths and the critical diameter for the transition between different DW types which agree well with direct simulations. Our results are useful for the experimental design of cylindrical nanowires for multiple applications. © 2021 Elsevier B.V.